2017
DOI: 10.1089/neu.2016.4550
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Phenotype Polygenic Risk Score Analysis of Persistent Post-Concussive Symptoms in U.S. Army Soldiers with Deployment-Acquired Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) contributes to the increased rates of suicide and post-traumatic stress disorder in military personnel and veterans, and it is also associated with the risk for neurodegenerative and psychiatric disorders. A cross-phenotype high-resolution polygenic risk score (PRS) analysis of persistent post-concussive symptoms (PCS) was conducted in 845 U.S. Army soldiers who sustained TBI during their deployment. We used a prospective longitudinal survey of three brigade combat teams to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…This suggests that in individuals who experience TBI, the physical insult to the brain and resulting alterations in structure and function may be influential contributors to the presentation of post TBI ADHD symptoms, whereas additive genetic predisposition contributes to developmentally acquired ADHD. These results oppose the idea that those with higher polygenic score may be more vulnerable to developing ADHD symptoms following brain injury but are consistent with a recent study of soldiers with TBI, that found that the genetic predisposition to persistent post-concussion symptoms following TBI does not have substantial overlap with genetic predisposition to neurodegenerative and psychiatric diseases (42).…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that in individuals who experience TBI, the physical insult to the brain and resulting alterations in structure and function may be influential contributors to the presentation of post TBI ADHD symptoms, whereas additive genetic predisposition contributes to developmentally acquired ADHD. These results oppose the idea that those with higher polygenic score may be more vulnerable to developing ADHD symptoms following brain injury but are consistent with a recent study of soldiers with TBI, that found that the genetic predisposition to persistent post-concussion symptoms following TBI does not have substantial overlap with genetic predisposition to neurodegenerative and psychiatric diseases (42).…”
Section: Discussionsupporting
confidence: 80%
“…Our investigation was conducted using summary statistics from GWAS of psychiatric disorders and testing for enrichment of positive selection signatures, using the same concept as is applied in high-resolution polygenic risk score analysis [ 26 , 27 ]. The positive selection signatures were identified using the hierarchical boosting (HB) algorithm, which is a machine-learning classification framework that combines the functionality of several selection tests to uncover different genetic features that are expected under selective sweeps [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the genes involved in immune response appeared to play a relevant role in the processes linked to allergic airway inflammation, lung function, and eczema-wheezing comorbidity. Further investigations of large cohorts, such Mendelian randomization studies 44 and polygenic risk score analysis 45 , can dissect how the genetics of lower lung function affects the risk of allergic disease.…”
Section: Discussionmentioning
confidence: 99%